2018
DOI: 10.1007/s10924-018-1236-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Molecular Weight on the Thermal Stability and the Miscibility of Poly(ε-caprolactone)/Polystyrene Binary Blends

Abstract: Poly(ε-caprolactone) (PCL) and two different molecular weight (6K and 650K) of polystyrene (PS) were mixed in solution to prepare binary blends of PCL/PS with various compositions. The impact of the molecular weight of PS in the blends was studied on thermal stability and miscibility by the thermogravimetric analysis (TGA) and the differential scanning calorimetry (DSC) method. The TGA results under dynamic conditions in an inert atmosphere show that the thermal stability of the blends depends on the length of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 30 publications
(33 reference statements)
0
18
0
Order By: Relevance
“…It can be concluded that due to the cleavage of the SF chains upon hydrolysis, SFNP with lower molecular weight exhibited lower thermal stability than the native SF. The strong dependence of the thermal stability on the length of the molecules was reported by Mamun et al [39].…”
Section: Thermal Characterizationmentioning
confidence: 54%
“…It can be concluded that due to the cleavage of the SF chains upon hydrolysis, SFNP with lower molecular weight exhibited lower thermal stability than the native SF. The strong dependence of the thermal stability on the length of the molecules was reported by Mamun et al [39].…”
Section: Thermal Characterizationmentioning
confidence: 54%
“…However, the most significant changes in the temperature of the onset of degradation assessed based on T 5% and T 10% were shown by the amorphous PLA variety with a low MFI (4032D). Interestingly, unlike the results of rheological tests, the 2500HP polymer showed the highest thermal stability as assessed by the TGA method, which may be associated with the high molecular weight of the polymer [64]. The high-MFI 3100HP and 3260HP PLA varieties showed comparable changes in thermal stability.…”
Section: Thermal Stability Of Extruded Pla Gradesmentioning
confidence: 62%
“…Generally, relatively large crosslinking density results in high decomposition temperature [29]. It can be seen in Figures S1, S3, and Table S1 that both IPDT and the rise with the increase of relative molecular weight of UHMWPE, indicating that the higher relative molecular mass UHMWPE has, the higher the internal physical entanglement density is and the better thermal stability UHMWPE has [34,35].…”
Section: 5mentioning
confidence: 93%